SLEEP DISORDERS AND DIVING-ASSOCIATED DECOMPRESSION SICKNESS - Harahap, Herpan Syafii; Indrayana, Yanna; Afif, Zamroni; Landapa, Raditya Rachman; Ismiana, Baiq Holisatul; Gea, Endah Irnanda Ulfa; Wiracakra, I Gusti Lanang Krisna (MNJ (Malang Neurology Journal), 2025)
Decompression sickness is considered as an important complication of deep diving. Since the trend of diving activities is increasing throughout the world and is dominated by novice divers, the incidence of decompression sickness should be high. Severe form of decompression sickness can cause damage to the central nervous system with varying manifestations of mild to severe neurological deficits. Recent studies show that sleep disorders need to be considered as an important consequence of decompression sickness. However, the pathophysiology of decompression sickness-associated sleep disorders is currently not well understood. Since sleep disorders are associated with dysfunction of anatomical structures and the neurotransmitter systems in the brain that regulate the sleep-wakefulness cycle, decompression sickness-associated sleep disorders can be postulated to be related to dysfunction of these two regulators of sleep-wakefulness cycle. Sleep disorders found in patients with decompression sickness are more likely to occur in type 2 decompression sickness and may be found in the form of insomnia, hypersomnia, circadian rhythm disorders, obstructive sleep apnea, and narcolepsy. This review aims to discuss the pathophysiology of sleep disorders and decompression sickness as well as possible mechanisms underlying sleep disorders in decompression sickness through theoretical approaches and the results of available studies. In conclusion, decompression sickness-related sleep disorders are thought to involve two pathological conditions in the brain, namely structural lesions and dysfunction of the neurotransmitter system in the brain.